Dynamic endothelial cell rearrangements drive developmental vessel regression. - Claudio A Franco; Martin L Jones; Miguel O Bernabeu; Ilse Geudens; Thomas Mathivet; Andre Rosa; Felicia M Lopes; Aida P Lima; Anan Ragab; Russell T Collins; Li-Kun Phng; Peter V Coveney; et al. (PLoS Biology)
Patterning of functional blood vessel networks is achieved by pruning of superfluous connections. The cellular and molecular principles of vessel regression are poorly understood. Here we show that regression is mediated by dynamic and polarized migration of endothelial cells, representing anastomosis in reverse. Establishing and analyzing the first axial polarity map of all endothelial cells in a remodeling vascular network, we propose that balanced movement of cells maintains the primitive plexus under low shear conditions in a metastable dynamic state. We predict that flow-induced polarized migration of endothelial cells breaks symmetry and leads to stabilization of high flow/shear segments and regression of adjacent low flow/shear segments.